2018
DOI: 10.3310/hta22740
|View full text |Cite
|
Sign up to set email alerts
|

Enteral lactoferrin to prevent infection for very preterm infants: the ELFIN RCT

Abstract: Background Infections acquired in hospital are an important cause of morbidity and mortality in very preterm infants. Several small trials have suggested that supplementing the enteral diet of very preterm infants with lactoferrin, an antimicrobial protein processed from cow’s milk, prevents infections and associated complications. Objective To determine whether or not enteral supplementation with bovine lactoferrin (The Tatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 68 publications
0
20
0
1
Order By: Relevance
“…A systematic review and meta-analysis reviewed nine RCTs and showed that prophylactic lactoferrin significantly reduced the incidence of late-onset sepsis and NEC (Bell's stage II or greater) [17]. Most recently, a large randomized control trial of 2203 infants contrasted these prior findings, demonstrating that enteral supplementation with bovine lactoferrin did not reduce NEC or the incidence of infection or mortality [18].…”
Section: Lactoferrinmentioning
confidence: 99%
“…A systematic review and meta-analysis reviewed nine RCTs and showed that prophylactic lactoferrin significantly reduced the incidence of late-onset sepsis and NEC (Bell's stage II or greater) [17]. Most recently, a large randomized control trial of 2203 infants contrasted these prior findings, demonstrating that enteral supplementation with bovine lactoferrin did not reduce NEC or the incidence of infection or mortality [18].…”
Section: Lactoferrinmentioning
confidence: 99%
“…He et al kamen in einem systematischenReviewderbisdahinveröffentlichtenrandomisierten Studien mit insgesamt 1834 Patienten zum Ergebnis, dass die oraleGabevonLaktoferrineinesignifikanteReduktionderKulturpositiven LOS, der NEC und der Mortalität durch Infektionen bewirkte [136]. Allerdings waren die in diesem Review eingeschlossenen Studien u. a. hinsichtlich der Inzidenz der Pilzsepsis sehr heterogen.IndernachdemReviewvonHeetal.veröffentlichten ELFIN Studie mit 2.203 Patienten hatte die Gabe von bovinem Lak-toferrinkeinenEinflussaufdasRisikoderLOS(RR0,95;95%CI0,86-1,04; p = 0,233) [137,138]. Somit kann nach aktuellem Stand die routinemäßige prophylaktische Gabe von bovinem Laktoferrin bei Frühgeborenen nicht empfohlen werden.…”
Section: Prävention Der Los Durch Laktoferrinunclassified
“…[8][9][10] Though several studies investigated multiple aspects of lactoferrin function, the underlying mechanism of its protective effect during NEC progression remains unclear, and its protective effects on the early stages of NEC is still controversial. 2,11 Therefore, we sought to elucidate the mechanisms driving lactoferrinmediated protection during NEC progression, especially focused on its regulation of inflammation and cell proliferation. Furthermore, we administered lactoferrin on healthy pup mice to verify its safety and test for adverse effects.…”
Section: Introductionmentioning
confidence: 99%